Gestão de projetos em um centro de pesquisa : diagnóstico e implantação de práticas para a agilidade - Piccirillo, Isabela Neto (2017)
Research centers are important for technologies development whose results could be innovative products. One of the difficulties that have arisen is in developing research projects with different professors in a multidisciplinary environment. Many authors have written about the importance project management skills, techniques and practices in research centers, but few show their applications and impacts. An action research was conducted to verify and select the root causes related to the challenges of project management in an international research center (Center for Research, Technology and Education in Vitreous Materials) through the Current Reality Tree. One of the main root causes found was about the lack of knowledge in project management methodology to elaborating multidisciplinary projects involving the transformation of a technology studied in an innovative product. Therefore, workshops were held to apply the Technology Roadmapping (TRM) and the product vision in a project that develops and intends to transform an innovative technology into a product. In addition, the Kanban approach was introduced for planning its main activities. The results from these applications of action research as well as the researchers' perception are discussed in detail.